Edukasi Dampak Penggunaan Cotton Buds untuk Membersihkan Telinga pada Siswa SMP YARI School Padang - Nadia Purnama Dewi; Ade Teti Vani; Irwan Triansyah; Dessy Abdullah; Rendri Bayu Hansah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Ears are one of the most frequently cleaned parts of the body. There are many ways to clean the ears, for example by using cotton buds, using candles and so on. The act of cleaning the ear with cotton buds is not recommended, because it can cause earwax (cerumen prop) to be pushed into the ear so that over time it will cause hearing loss (deafness). Sometimes the use of cotton buds is too deep, causing damage to the eardrum. Education in the form of counseling given to junior high school students aims to reduce the risk of ear damage from an early age due to the use of cotton buds and how to clean the ears properly. Education is held at SMP Yari School Padang. The extension method uses power points and leaflets which are distributed to school students. At the time the counseling was carried out, pretest and posttest were given to see students' knowledge of the material presented. The results of the pretest and posttest showed an increase in students knowledge about the material that had been given with p value=0,000.